2013
DOI: 10.4236/jep.2013.41b015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dissolved Heavy Metal Pollution in Five Provinces of Zambia

Abstract: Zambia’s economy is hinged on mining activities with Cu being the main metal. Zn and Pb were mined at one point in Kabwe town. There are also known deposits of Co and Mn. The study focused on comparing heavy metal pollution from different regions across Zambia with a view of determining the impact of the stage of social development and economic activities on the environment. The water analysed was obtained near dump sites,farmlands, pit latrines, water reservoirs or dams, major rivers and small streams that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…In this study, we investigated the effects of environmentally relevant levels of Pb (as reported in Kabwe town and Zambia (Nachiyunde et al, 2013) on ensuing subcellular oxidative stress responses of the primary antioxidant, pro-apoptotic and anti-apoptotic genes and locomotor behaviour of larval zebrafish. Acute Pb exposure to larval zebrafish for 30 minutes induced hyperactivity characterised by significant increases in distance covered, swimming speed and mobile frequency as well as increased distance covered and speed under light illumination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we investigated the effects of environmentally relevant levels of Pb (as reported in Kabwe town and Zambia (Nachiyunde et al, 2013) on ensuing subcellular oxidative stress responses of the primary antioxidant, pro-apoptotic and anti-apoptotic genes and locomotor behaviour of larval zebrafish. Acute Pb exposure to larval zebrafish for 30 minutes induced hyperactivity characterised by significant increases in distance covered, swimming speed and mobile frequency as well as increased distance covered and speed under light illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from domestic animals like cattle, goats, free range chickens and wild rodents within the vicinity of the closed mine had substantial Pb accumulation in their tissues (Nakata et al, 2016;Yabe et al, 2013Yabe et al, , 2011. On the other hand, Pb levels in natural water bodies and ground water drawn from boreholes in the area were found to have the highest concentration of 94 µg/L from a given site with the average concentration of 3 µg/L, well below the Pb permissible values of 50 µg/L by the Zambia Bureau of Standards (Nachiyunde et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are only a handful of case studies which have characterised the impacts of waste dumps and industry in urban areas and these are dominated by examples from Nigeria. Examples of contamination from historical mining activity come from Nigeria (Ezekwe et al 2012) and Zambia (Nachiyunde et al 2013a). …”
Section: Chemical Contaminantsmentioning
confidence: 99%
“…A study by Nachiyunde et al (2013a) included sites from the Copperbelt in Zambia and found overall low contamination levels in groundwaters with no trace elements above WHO drinking-water guideline values. von der Heyden and New (2004) also carried out a detailed study in the Zambian Copperbelt on the impact of mine tailings on groundwater quality.…”
Section: Chemical Contaminantsmentioning
confidence: 99%